Factors Determining Callbacks to Job Applications by the Unemployed: An Audit Study - Henry S Farber; Dan Silverman; Till von Wachter (Institute for the Study of Labor (IZA), 2015)
We use an audit study approach to investigate how unemployment duration, age, and holding a low-level "interim" job affect the likelihood that experienced college- educated females applying for an administrative support job receive a callback from a potential employer. First, the results show no relationship between callback rates and the duration of unemployment. Second, workers age 50 and older are significantly less likely to receive a callback. Third, taking an interim job significantly reduces the likelihood of receiving a callback. Finally, employers who have higher callback rates respond less to observable differences across workers in determining whom to call back. We interpret these results in the context of a model of employer learning about applicant quality.
Keywords: J64; 330; audit study; unemployment duration; interim job; age discrimination